THE ROLE OF CONTRACTUAL PRINCIPLES IN CONTEMPORARY EMPLOYMENT RELATIONSHIPS IN GERMANY: IS THERE A LESSON TO LEARN FOR SOUTH AFRICA? PART 1 - Marlize Ingrid van Jaarsveld (Obiter, 2022)
An employment contract is preceded by the conclusion of a valid contract between an employee and an employer. Prior to the commencement of an employment relationship the parties must be in agreement as regards the terms of their contract. It was traditionally accepted that the parties entered into a contract in the hope of securing reciprocal advantages for themselves, and that the parties accordingly should be able to contract on the terms they desired. This argument lost momentum seeing that the employment relationship became even more curtailed by various statutory provisions. Likewise, the contractual freedom of employers and employees alike to determine the terms of their contractual relationship has been limited in Germany by various enactments. The role and impact of traditional contractual principles as they present in contemporary employment relationships in Germany are explored in this article, ultimately to determine whether these principles remain significant at all. It is established that these traditional contractual principles, emanating from an employment relationship, not only remain essential, but moreover continue to feature in contemporary employment relationships in Germany in a distinctive and unique way. Furthermore the on-going interaction between these contractual principles and the provisions of statute is regarded as valuable for employment relationships in South Africa.